Substitution of wheat flour with purple sweet potato and red bean increased energy value, protein, and fat content of muffin: Substitusi Terigu dengan Ubi Ungu dan Kacang Merah Meningkatkan Nilai Energi, Protein, dan Lemak Muffin - Berylia Sendya Dwi Putriani; Aprilia, Veriani; SAlfarino, Ryan (JITIPARI, 2025)
Muffin is a wheat flour-based snack with gluten content and high glycemic index, so substitution is needed to reduce the impact of excess consumption on health. The ingredients used are purple sweet potato and red bean which have high content of energy, carbohydrates, protein and low GI. The study aimed to determine the effect of substituting wheat flour with sweet potato flour and red bean flour on the nutritional value of muffins. This was an experimental study with a single-factor completely randomized design (CRD) with one control group and three treatment groups with the proportion of wheat flour: purple sweet potato flour: red bean flour namely 100:0:0 (P0), 30:20:50 (P1), 30:35:35 (P2), dan 30:50:20 (P3). They were repeated 3 times.  The results showed that there was an effect of wheat flour substitution with sweet potato flour and red bean flour on the nutritional value of muffins (p<0.001). The highest average nutritional value of each treatment is water content P3 (34.45%), ash content P3 (3.06%), protein P1 (9.92%), fat P1 (9.39%), carbohydrate P3 (44.67%), and energy P1 (294.23 kcal). The nutritional value of 50g muffins is in accordance with the quality standards according to SNI and the standard requirements for children, but the fat content is above the standard if it is consumed as snacks for DM patients, therefore it needs to reformulate to fulfill the standard.